Penanaman Nilai-Nilai Karakter Melalui 7 Kebiasaan Anak Indonesia Hebat - Mukarromah Mukarromah (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
Implementing character values through the 7 Habits of Great Indonesian Children is crucial for developing a disciplined, healthy, religious, and socially conscious young generation from elementary school age. Students at Masyithoh IBS Glagahsari Sukorejo Elementary School still face various challenges such as low discipline, the habit of buying instant snacks, feeling sleepy while studying, and a lack of interest in reading. Therefore, this community service program focused on internalizing seven key habits: waking up early, praying, exercising, eating healthy and nutritious food, a love of learning, being social, and going to bed early. The goal of the activity was to instill positive lifestyles that support learning and character building. The steps used included observation, seminars, program implementation, and evaluation involving teachers, students, and parents. The results showed improvements in time management, study concentration, the habit of bringing healthy lunches, and consistency in worship and exercise. This program has proven to be simple, applicable, and effective, although it still requires intensive guidance to maintain consistency.